ISH NIA PS 03-09 Plasma fatty acids as biomarkers of hypertension development over 5-years: a longitudinal study in black South Africans. (September 2016) - Zec, Manja; Richter, Marilize; Baumgartner, Jeannine; Schutte, Aletta; Smuts, Cornelius
Abstract : Objective: We investigated the association between plasma phospholipid fatty acids (FA) and hypertension (HT) in 711 apparently healthy black South African adults. Design and method: Study is part of the multinational Prospective Urban Rural Epidemiological study, investigating health implications of urbanization in apparently healthy populations. We performed multivariate prospective (PRA) and longitudinal (LDA) analysis. PRA explored the association of baseline (2005) FA with development of HT at follow-up (2010) from subjects normotensive at baseline, by applying logistic regression. LDA assessed association of change in FA with HT over 5-years (2005–2010), by including the data from both time-points, using Generalized Estimating Equations. Both analyses were adjusted for urbanization factor, gender, age, HIV status, smoking, HT medication use, waist circumference, gamma-glutamyl transpeptidase, glucose, hsCRP, HDL-c, creatinine clearance, urinary albumin/creatinine ratio, and systolic blood pressure. Statistical analysis was performed in SAS ver. 9.4. Results: 19.2% of baseline normotensive subjects developed HT over 5-years. We analyzed in separate multivariate models the contribution of individual FA (palmitic acid (PA), stearic acid (SA), oleic acid (OA), eicosapentaenoic acid (EPA), docosohexaenoic acid (DHA) and trans-elaidic acid (EA)), and FA composite biomarkers. In LDA, PA (OR = 0.92, p = 0.02) and EA (OR = 1.45, p = 0.01) contributed to HT development over the 5-years, and when OA was excluded from the model, SA reached significance as well (OR = 0.88, 95%CI:0.80–0.97, p = 0.01). In LDA, total saturated, monounsaturated and polyunsaturated FA significantly (p < 0.05) contributed to HT (OR = 0.67, 0.74 and 0.70, respectively). In PRA, DHA was significantly associated with HT (OR = 1.37, p = 0.04). Oppositely, LDA showed that the unit of DHA non-significantly decreases odds for HT development for 11 and 15%, for models with and without OA. Conclusions: Our results indicate a protective association of SA with HT development over 5-years in black South Africans. The association is confounded by OA, the metabolic product of SA, challenging dietary requirements of saturated fats in the population. Figure. No caption available.